Three new species of myrmecophilous scutacarid mites (Acari: Scutacaridae) from Western Siberia, Russia - Khaustov, Alexander A. (Zootaxa, 2015)
Three new species of myrmecophilous mites of the genus Scutacarus Gros, 1845 (Acariformes: Pygmephoroidea: Scutacaridae), S. lasiophilus sp. nov., S. myrmicinus sp. nov., and S. crinitus sp. nov. are described from ants and their nests in Tyumen Province, Western Siberia, Russia.